2016
DOI: 10.5114/aoms.2016.62868
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between C-reactive protein and cognitive functions according to APOE gene polymorphism in post-menopausal women

Abstract: IntroductionA potential factor increasing the risk of the development of cognitive impairment with age is apolipoprotein E (APOE) ε4 carrier status. A subsequent factor which may increase the risk of development of cognitive impairment at an older age is the concentration of C-reactive protein (CRP). The objective of the study was to examine the relationship between cognitive functions and the concentration of CRP in post-menopausal women who were carriers of particular apolipoprotein E gene (APOE) polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…Our findings further align with the growing literature that patients with more severe delirium are at highest risk for cognitive decline, 52 and it adds to the expanding knowledge of the complexity of gene functional networks, including gene-protein interactions. [53][54][55] Our results align with previous work on gene-protein interactions in delirium and AD. These findings (e.g., Ref.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings further align with the growing literature that patients with more severe delirium are at highest risk for cognitive decline, 52 and it adds to the expanding knowledge of the complexity of gene functional networks, including gene-protein interactions. [53][54][55] Our results align with previous work on gene-protein interactions in delirium and AD. These findings (e.g., Ref.…”
Section: Discussionsupporting
confidence: 89%
“…found CRP to be the only mediator of this relationship after correction for multiple comparisons. Similarly, an APOE × CRP interaction has been reported for cognitive function among postmenopausal women and 4‐year decline in cognitive function in community‐dwelling older adults . Taken together, our finding of a gene‐protein interaction between APOE and CRP on postoperative delirium fit well with the studies of gene‐protein interactions on AD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…CRP has been associated with subsequent cognitive impairment and age-related cognitive decline, whereas the E4 allele, which was associated with low CRP, increases the risk of cognitive reduction and Alzheimer disease [ 5 , 6 , 41 , 42 ]. The interactions between CRP, the APOE genotype, cardiovascular diseases and cognitive functions and dementia are confusing and might depend on gender, age, and disease such as obesity [ 43 46 ]. The association between CRP and atherosclerosis might be diminished in subjects with obesity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the presence of some depressive symptoms has a significant effect on cognitive impairment, which is increased in APOE ε4 carriers [ 29 ]. It was also demonstrated that in post-menopausal women the correlation between CRP level and cognitive functions may be modified by apolipoprotein E genotypes [ 30 ]. In addition, an enhanced negative effect of testosterone on cognition was found in postmenopausal women with at least one APOE ε4 allele [ 31 ].…”
Section: Discussionmentioning
confidence: 99%